The separation and conflicting custody dispute and the damage for children - Tsunemi Negrão, Natalia (2019)
The present research aims to analyze seven cases of custody dispute verified by a forensic psychologist in a county South of Brazil, where were observed substantial damage and/or alienation in the relationship between child and one of parents. A documentary retrospective study was conducted, which sought the categories most frequently found in each of the cases. It was noted that when one of parents does not accept the separation and remains in custody of children, it is possible this initiates a process of growing apart of the child with the ex spouse, which can cause serious harm to child development. The main damage observed were: aggression, depression, anxiety, use of lies to communicate, rejecting the parent who does not have custody, and even incorporating phrases of the parent who obtained custody as if they were their own.